Implementasi Asas Dekonsentrasi Dalam Kabupaten Mamuju, Sulawesi Barat - Hanny Wulandari Yasin; Tomy Michael (UIN Syarif Hidayatullah Jakarta, 2022)
Regional autonomy evolved from efficiency and growth to independence and justice after Indonesia's reformation. Expansion occurs. Social and political elites complicated the legal division of this territory. Regional expansion was a Reformation-era legal phenomenon. West Sulawesi grew regionally. Law 26 of 2004 deconcentrated West Sulawesi. This study evaluates whether West Sulawesi has implemented deconcentration and complied with Law 26 of 2004. In this study, Mamuju Regency, the capital of West Sulawesi province, represents the region's law implementation. This research assesses Mamuju Regency's implementation and law compliance. Mamuju Regency's 141 regional regulations promote government, community, and development services. This is seen in Mamuju Regency's DPMPTSP system and health insurance. Governance, development, and social issues are Mamuju Regency's priorities.